Detection of basal stem rot (BSR) infected oil palm tree using laser scanning data - Bejo, Siti Khairunniza; Vong, Chin Nee (Elsevier, 2014)
Basal Stem Rot (BSR) is a well-known disease that affecting the production of oil palm. Early disease detection is vital to manage the disease effectively. This study examined the potential use of Terrestrial Laser Scanning (TLS) data to analyse the properties of oil palm tree at canopy and trunk section for non-infected and infected BSR at different severity level of infection. In summary, area and perimeter at trunk section 150 cm; and size of canopy shows significant relationship with the severity level of BSR with the Pearson correlation value of -0.571, -0.530 and -0.806, respectively.